2022
DOI: 10.3390/ijerph191710646
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying and Post-Traumatic Stress Disorder Symptomology: The Influence of Role Conflict and the Moderating Effects of Neuroticism and Managerial Competencies

Abstract: Research has explored numerous consequences of workplace bullying, including a recent link to the exhibition of post-traumatic stress disorder (PTSD) symptomology. Role conflict as a workplace stressor may contribute to instances of bullying from a passive perspective, which may lead to PTSD symptomology in victims. What remains less explored is if role conflict has a direct relationship to PTSD symptomology and how personality traits such as neuroticism and workplace factors such as managerial competencies ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…In agreement with the existing literature, the research results reveal that negative workplace environment, descripted by negative atmospheric conditions, poor equipment, tools and technology, poor co-worker relationships and high work stress affect employees' mental health (Anjum et al, 2018). In addition, studies investigating workplace bullying and victimization, found that workplace environment stressors, relate to bullying and victimization at work (Chenevert et al, 2022).…”
Section: Workplace Bullying and Victimization And The Role Of Workpla...supporting
confidence: 86%
See 1 more Smart Citation
“…In agreement with the existing literature, the research results reveal that negative workplace environment, descripted by negative atmospheric conditions, poor equipment, tools and technology, poor co-worker relationships and high work stress affect employees' mental health (Anjum et al, 2018). In addition, studies investigating workplace bullying and victimization, found that workplace environment stressors, relate to bullying and victimization at work (Chenevert et al, 2022).…”
Section: Workplace Bullying and Victimization And The Role Of Workpla...supporting
confidence: 86%
“…Under negative and distressing working conditions, highly neurotic employees may engage in annoying behaviours more often, which could lead potential perpetrators to bully them, and treat them unjustly. In particular, in organizations where employees are dissatisfied with the work environment, are more likely to be involved in interpersonal conflicts which may then escalate into bullying and victimization, especially for those with more ''vulnerable'' characteristics, such as neuroticism (Balducci et al, 2011, Chenevert et al, 2022.…”
Section: Workplace Bullying and Victimization And The Role Of Workpla...mentioning
confidence: 99%
“…Another very important factor predicting PTSD in pediatric healthcare workers is the presence of workplace bullying, as indicated by our research findings. According to Chenevert [ 45 ], bullying is a factor that increases work-related stress, as it causes changes in the physical and mental conditions of the worker in response to life-threatening situations, such as challenges and threats. Additionally, Brande [ 46 ] defends that the consequences of workplace bullying are much more destructive than the consequences of all other occupational stressors combined.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive levels of stress are generally damaging for individuals and organizations. It holds severe negative consequences for performance of the employees (Banerjee & Mehta, 2016;Chenevert et al, 2022;Fahmi et al, 2022;Huo & Jiang, 2023;Rijanto, 2023). The victims of stress in any organization feel and look depressed, nervous, and emotionally damaged, who cannot meet the challenging tasks (Bakker & Demerouti, 2007;Iskamto, 2021;Pradoto, Haryono, & Handari, 2022;Tehreem, Parveen, & Shams, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The stress may be caused by issues at the workplace or certain family problems. The issues at workplace may include workload, task ambiguity, uncivil behaviors, or poor environment (Chenevert, Vignoli, Conway, & Balducci, 2022). Similarly, prolonged working hours at workplace may affect the home commitments, thereby creating a conflict at home (Allen, French, Dumani, & Shockley, 2022;Dodanwala, Santoso, & Shrestha, 2022).…”
Section: Introductionmentioning
confidence: 99%